MINAT BELI KONSUMEN MELALUI APLIKASI TIX ID YANG DIPENGARUHI OLEH SOCIAL MEDIA MARKETING, BRAND IMAGE, DAN E-SERVICE QUALITY: Studi Pada Aplikasi Tix Id di Kota Bandung - Setiawati, Devia; Madiawati, Putu Nina (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2020)
Information technology in Indonesia continues to increase, this is in line with the increasing film industry in Indonesia is also increasingly rapid. One of them appeared online ticket purchase service application, Tix Id. This study aims to find how social media marketing, brand image, e-service quality, consumer purchase intention in the Tix Id application, and how is the partial influence of social media marketing, brand image, and e-service quality on consumer purchase intention in the Tix Id application. This study uses data analysis methods Structural Equation Modeling using the SmartPLS data processing application. The results of descriptive analysis based on respondent responses to social media marketing, brand image, e-service quality, and purchase intention are included in good categories. The results of hypothesis testing based on t-statistic value of the data processing results show that all hypotheses were accepted. Keywords: social media marketing, brand image, e-service quality, and purchase intention.